The structure of the modern „Great novel" - Ivinskis, P. (Literatūra, 1969)
The modern „great novel" is created on an objective base which shows that the truth of modern history is impossible without description of man-creator. There is no man outside history and history is the forming environment to man. The innovation of form is born due to the experience of the novelist. In the novel-epopee and monumental novel of the ’30ties and the ’40ties there was proved that man is determined by history. But in the novels mentioned above one can find a new thesis: history is created by man. This is a new essential change in the interpretation of the relation between history and a person. And this fact brought something new to the modern „great novel", to its subject, composition and psychology.